Os efeitos jurídicos da boa-fé subjetiva nas famílias simultâneas - Santana, Carla Rodrigues de (2012)
The courts have been asked to solve cases involving the phenomenon of simultaneous families, as the extraordinary appeal number 397.762-8, judged in 2008, by the Brazilian Supreme Court (STF). This present work intends to demonstrate that the Brazilian privet judiciary system has conditions to give legal effects to the phenomenon of simultaneous families, when relating the hypothesis of objective good faith of one of the partner, different than those provided by the application of the partnership at a will theory which comes from the Precedent 380 of Brazilian Supreme Court (STF). To reach this aim the deductive and inductive processes (research modality) were used to analyze the following instrumental proceedings: collection of information brought from the doctrinal books; final courts decisions from the state and superior courts, updated data about social behaviors published on magazines; articles; academic dissertations and thesis. Thus, this work aggregates the historical evolution (jurisprudential and legislative) of the marriage by habit in Brazil. It points the elucidations about the comparative law, analyzing the legislative treatment given by France, Spain, Portugal, Bolivia, Peru, Panama, Cuba and Argentina. It mentions the general aspects about the monogamy principles and the legal conclusions from its violation. It brings final courts decisions in which analyze the phenomenon of the simultaneous families. It presents: considerations about the privet juridical system; the Federal Constitution of 1988 as a source of the civil law and the efficiency of the fundamental rights when relating facto and privet judicial situations; the topic and the new systematic thought. It brings the subjective good faith and the human dignity as ways of relativization of the binding rules given to the simultaneous families in the marriages by habit. It clarifies the proceeding instruments to prove the subjective good faith. It shows the doctrinal and jurisprudential understanding about the possibilities of the recognition of the putative marriage by habit by the analogy of the putative marriage (article 1.561 of the Civil Code of 2002)